2001
DOI: 10.1097/00000637-200107000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Flora of Hirudo medicinalis and Their Antibiotic Sensitivities in the Middle Black Sea Region, Turkey

Abstract: The rate of infectious complications of leech therapy is almost 20% because Hirudo medicinalis has endosymbiotic bacteria. The aim of this study was to determine the bacterial flora of H. medicinalis and their antibiotic sensitivities in a region in Turkey. Sixteen adult leeches were collected in Middle Black Sea region, Turkey. They were rubbed onto blood agar plates directly under ether anesthesia to obtain surface cultures. They were then killed to obtain mouth and gut cultures. Culture swabs were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…Subsequent studies supported the presence of one dominant microbe, an Aeromonas species which was consistently present in medicinal leeches, but disagreed in two aspects, i.e., the identity of the Aeromonas species and the presence of other microbes in the leech midgut (11,12,14,29). Case reports identified Aeromonas hydrophila infections associated with the clinical use of medicinal leeches, but these studies often used commercial phenotypic tests that do not accurately identify Aeromonas to the species level (1,7,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies supported the presence of one dominant microbe, an Aeromonas species which was consistently present in medicinal leeches, but disagreed in two aspects, i.e., the identity of the Aeromonas species and the presence of other microbes in the leech midgut (11,12,14,29). Case reports identified Aeromonas hydrophila infections associated with the clinical use of medicinal leeches, but these studies often used commercial phenotypic tests that do not accurately identify Aeromonas to the species level (1,7,29).…”
mentioning
confidence: 99%
“…A second controversial point has been the complexity of the midgut microbiota. A few studies implementing nonquantitative approaches reported the presence of additional bacterial species in the midgut (11), while other studies reported only Aeromonas spp. (14).…”
mentioning
confidence: 99%
“…From the leech crop, researchers repeatedly isolated a pure culture of an Aeromonas species which we identified as Aeromonas veronii bv. sobria (␥-Proteobacteria, Aeromonadaceae) and had reported that only this bacterium inhabits the leech digestive tract (11,12,15,29). Recently, a PCR-based approach discovered the presence of a second symbiont, an "unculturable" Rikenella-like bacterium (clone PW3, with an 89.7% 16S rRNA gene identity to Rikenella microfusus [Bacteroidetes, Rikenellaceae]), in the crop (42).…”
mentioning
confidence: 99%
“…In contrary, a study performed by Eroglu and colleagues which implemented a non-quantitative approach, reported the presence of additional bacterial species in the midgut, besides Aeromonas sp [69].…”
Section: Leech Gut and Body Surface Microfloramentioning
confidence: 86%